Development of Religiosity Measurement Tools for High School Students in the Evaluation of Islamic Religious Education Learning - Sadiah, Sadiah; Mujahidin, Endin; Lisnawati, Santi (Fakultas Ilmu Pendidikan Universitas Negeri Padang, 2025)
This research aims to develop an instrument to measure the religiosity of high school students in the context of Islamic Religious Education learning evaluation. The background of this research is based on the fact that learning evaluations so far tend to focus on cognitive aspects, while the affective and psychomotor dimensions have received less attention. This research uses a Research and Development (R&D) approach with the ADDIE (Analysis, Design, Development, Implementation, Evaluation) development model. The instruments were compiled based on the synthesis of various theoretical models of religiosity, such as those of Glock and Stark, Mahudin et al., and Olufadi. Validation is carried out by experts in the fields of Islamic education, educational psychology, and language. The results showed that this instrument met the theoretical and empirical standards, with a feasibility score of 97.7% from Islamic Religious Education experts, 100% Indonesian linguists, and 92% from educational psychologists, with an average score of 94%. This shows that the instrument is very feasible to use to assess the integration of religious values in the evaluation of PAI learning. Keywords: Measuring Tools, Learning Evaluation, Islamic Religious Education, Religiosity.